2020
DOI: 10.3390/ijerph17134876
|View full text |Cite
|
Sign up to set email alerts
|

A New Nasal Restriction Device Called FeelBreathe® Improves Breathing Patterns in Chronic Obstructive Pulmonary Disease Patients during Exercise

Abstract: A device called FeelBreathe (FB)® was designed, developed, and patented for inspiratory muscle training. The main aim was to determine the acute responses on lung ventilation, gas exchange, and heart rate during exercise in patients with chronic obstructive pulmonary disease (COPD) with and without the use of FB. In this study, a randomized cross-over trial was performed with 18 men diagnosed with COPD (FEV1 between 30% and 70% of its predicted value). Each participant randomly conducted two trials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Exp: 521/15/EC, Spain) ( Figure 1 ). The use of this device during exercise has been used in previous investigations, both in athletes [ 13 ] and in patients with COPD [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exp: 521/15/EC, Spain) ( Figure 1 ). The use of this device during exercise has been used in previous investigations, both in athletes [ 13 ] and in patients with COPD [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exp: 521/15/EC, Spain) (Figure 1). The use of this device during exercise has been used in previous investigations, both in athletes [13] and in patients with COPD [16,17]. Participants were randomly assigned to either the cycling training combined with FB (FB, n = 10) or control group without FB (Control, n = 8).…”
Section: Training Programmentioning
confidence: 99%
“…Gonzalez-Montesinos et al studied this circumstance and observed that patients who have used FeelBreathe ® together with a pulmonary rehabilitation program show an improvement in quality of life, dyspnea, exercise capacity, and inspiratory muscle strength. However, the main limitation of these studies is the small number of patients, so more studies are needed to reach a definitive conclusion on the addition of FeelBreathe ® in a pulmonary rehabilitation program [31,55,56].…”
Section: Feelbreathe ®mentioning
confidence: 99%
“…Depending on the size and porosity of the device material, the inspiratory process is more or less difficult. This device has the possibility of using it not only in a static situation but also dynamically during exercise [31]; 3.…”
mentioning
confidence: 99%
“…The larger one makes inspiration more difficult. Previous studies in COPD patients using FB have reported improvements in ventilatory efficiency and pattern, as well as increased inspiratory and expiratory time during exercise [ 12 ]. FB has also been reported to provide improvements in dyspnea, quality of life, exercise tolerance and inspiratory muscle strength after using it in an 8-week pulmonary rehabilitation programme [ 13 ].…”
Section: Introductionmentioning
confidence: 99%